The effect of modern Iranian family culture towards high-density vertical development housing design - Nayyerifallah, Siyamak (2015)
Housing is one of the ways in which a product of architecture can accommodate a family culture. Modern middle-class Iranian families face great difficulties in adjusting their culture to their modern vertical housing since the latter is completely modelled from Western culture. The main objective of this study is to provide guidelines for the design of highdensity vertical housing that would suit the Iranian middle class family culture. Accordingly, this study highlights the common patterns associated with the daily routine of middle-class Iranian families, their occasional rituals, and the existing problems they face in regard to their daily rituals, cultural activities, and religious rites when living in modern vertical housing. By focusing on the possibilism theories, this qualitative descriptive research selected the strategy of multiple case studies under constructivism paradigm. The data collection methods include direct observation, semi-structured single face-to-face interviews (n=13), semi-structured focus group interviews (n=9), and photograph taking. In regard to the saturation criterion in the data collection procedure, 16 Iranian middle-class families in the new city of Parand, and the symbol of future Iranian cities, were studied. The collected data were analysed through descriptive, qualitative content and via plan layout analysis methods. The findings consist of descriptions of the life patterns of studied families within the modern vertical house setting. Space limitations of modern housing units suggest reducing the size of the bedroom so that non-related activities can be transferred to the living room. Besides, simple rectangle of the living room and the kitchen must be divided into several smaller areas with possible integration to support the aforementioned transferred activities. Additionally, the hierarchy of sight and physical accessibility will be enhanced through provision of a private family circulation way. Conclusively, the suggested modern Iranian vertical housing is more suited to the lifestyle of middle-class Iranian families by only 20% area growth in comparison to the existing vertical housing.